Writing across difference : theory and intervention - Daniel, James Rushing; Malcolm, Katie; Rai, Candice, 1976- (Utah State University Press, 2022)
"Increasingly divided by economic inequality, racial injustice, xenophobic violence, and authoritarian governance, writing studies scholars have developed responsive theories and practices to engage students, teachers, administrators, and citizens. The first collection to focalize difference as such, gathering scholars offering theoretical, methodological, and pedagogical resources for understanding, interrogating, negotiating, and writing across difference"--